2017
DOI: 10.1149/08008.0335ecst
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxygen Transport Resistance Components and Water Transport Phenomena with Hydrophilic and Hydrophobic MPL in PEFC

Abstract: This paper investigated the mechanism of water and oxygen transport phenomena in the vicinity of a micro-porous-layer (MPL). The influence of contact firmness between the MPL and a catalyst layer (CL) on the transport was evaluated quantitatively by analyzing oxygen transport resistance components. For the analysis, the limiting current method was extended to flooding conditions. These investigations were conducted with each of hydrophobic and hydrophilic MPLs. With low contact firmness, oxygen transport resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The pressure independent resistance can be assumed to correspond approximately to the oxygen transport resistance in the CL, the Knudsen diffusion resistance in the pores of the CL, and the transport resistance from the gas in the pores to the Pt surface through the ionomer, and this allows the oxygen transport resistance in the CL to be evaluated quantitatively. The results suggest that the oxygen transport resistance in the CL with the hydrophilic CF-MPL is maintained lower than that with the hydrophobic CB-MPL at high current densities, 22 supporting the experimentally suggested water transport illustrated in Fig. 10 that the hydrophilic CF-MPL promotes the draining of water from the CL to the MPL.…”
Section: Ice Distributions In the Four Types Of The Mplssupporting
confidence: 80%
See 2 more Smart Citations
“…The pressure independent resistance can be assumed to correspond approximately to the oxygen transport resistance in the CL, the Knudsen diffusion resistance in the pores of the CL, and the transport resistance from the gas in the pores to the Pt surface through the ionomer, and this allows the oxygen transport resistance in the CL to be evaluated quantitatively. The results suggest that the oxygen transport resistance in the CL with the hydrophilic CF-MPL is maintained lower than that with the hydrophobic CB-MPL at high current densities, 22 supporting the experimentally suggested water transport illustrated in Fig. 10 that the hydrophilic CF-MPL promotes the draining of water from the CL to the MPL.…”
Section: Ice Distributions In the Four Types Of The Mplssupporting
confidence: 80%
“…10 that the hydrophilic CF-MPL promotes the draining of water from the CL to the MPL. Although the above results are limited to a specific condition and further detailed analyses such as the limiting current 22 and oxygen gain 23 analyses are necessary for a more precise evaluation of the oxygen transport resistance in the CL, it may be concluded that the hydrophilic CF-MPL enhances the transport of liquid water in the CL due to the hydrophilic fibers. The MPL structure with the large pores and sufficient thickness provides a superior environment to evaporate the water in the MPL, and this results in the better anti-flooding performance at high current densities, as shown in the comparison of the cell performances (Figs.…”
Section: F491mentioning
confidence: 96%
See 1 more Smart Citation
“…However, PTFE was neglected and not fully reconstructed in their work. Hannach et al [ 22 ] obtained a realistic 3D MPL microstructure, Lee et al [ 17 ], Deng et al [ 28 ], Bock et al [ 8 ], Aoyama et al [ 29 ], and Nozaki et al [ 30 ] studied the transport of gas-water-heat-electricity in MPL. However, only a few of the published works considered the effect of mechanical compression on the MPL transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effects of relative humidity and current density on liquid water accumulation and oxygen transport resistance were investigated (2). Our previous study extended the limiting current method to flooding conditions, and analyzed quantitatively the effects of condensed water on the resistance components of oxygen transport inside and outside the catalyst layer (CL) (7). It was also reported that a hydrophilic MPL with carbon fiber (CF) and ionomer has the effect of wicking liquid water from the CL under flooding conditions, and its performance is improved compared to a hydrophobic MPL with carbon black (CB) (8).…”
Section: Introductionmentioning
confidence: 99%